Synergistic Protection of Mice against Plague with Monoclonal Antibodies Specific for the F1 and V Antigens of Yersinia pestis - Hill, Jim (American Society for Microbiology, 2003)
Monoclonal antibodies specific for Yersinia pestis V antigen and F1 antigen, administered singly or in combination, protected mice in models of bubonic and pneumonic plague. Antibodies showed synergy when administered prophylactically and as a therapy 48 h postinfection. Monoclonal antibodies therefore have potential as a treatment for plague.